Histology for pathologists - Mills, Stacey E. (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins Health, 2012)
"This new edition also brings quite a few new authors and their fresh perspectives, sadly necessitated in several instances by the deaths of former world-class senior contributors. Those no longer with us include, Drs. Margaret Billingham, John McNeal, and Sunitha Wickramasinghe. Shortly after submission of his chapter for this edition, my friend Dr. Bernd Scheithauer also left us"--Provided by publisher.
Includes bibliographical references and index
Keywords: Histology, Pathological; Pathology; Histology; Pathology